1991
DOI: 10.1128/aac.35.9.1875
|View full text |Cite
|
Sign up to set email alerts
|

Comparative inactivation of isepamicin, amikacin, and gentamicin by nine beta-lactams and two beta-lactamase inhibitors, cilastatin and heparin

Abstract: This study was undertaken to compare the susceptibility to inactivation of isepamicin with amikacin and gentamicin when. exposed to different beta-lactams, ,I-lactamase inhibitors, and heparin. The aminoglycosides (5; 10, 20, and 50 ,g/ml) were incubated in human serum with ampicillin, azlocillin, aztreonam, carbenicillin, ceftazidime, piperacillin, and ticarcillin (100 and 600 ,ug/ml) and with clavulanate, cilastatin, 1:1 imipenemcilastatin? oxacilin, and sulbactam (20 and 120 ,ug/ml) for 48 h at 37°C. Amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…DISCUSSION Aminoglycosides have been used with extended-spectrum penicillins to provide wider antibacterial coverage against gram-negative bacilli through a synergistic effect (2,3,16,25,31,32). It is known, however, that the combined use may result in chemical inactivation of the aminoglycoside, leading to a loss in antibiotic activity (12,28). In vitro studies have demonstrated that the rate of inactivation is related to the incubation period, temperature, presence of solutes, and ,-lactam concentration (6,11,12,(21)(22)(23).…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…DISCUSSION Aminoglycosides have been used with extended-spectrum penicillins to provide wider antibacterial coverage against gram-negative bacilli through a synergistic effect (2,3,16,25,31,32). It is known, however, that the combined use may result in chemical inactivation of the aminoglycoside, leading to a loss in antibiotic activity (12,28). In vitro studies have demonstrated that the rate of inactivation is related to the incubation period, temperature, presence of solutes, and ,-lactam concentration (6,11,12,(21)(22)(23).…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…Plazomicin against carbapenem susceptible A. baumannii (n = 8) and carbapenem resistant A. baumannii (n = 69) showed MIC values ranging from 0.5-16 μg/mL and 0.5-64 μg/mL, respectively (40). The AG inactivation by beta-lactam antibiotics has been observed in vivo and in vitro (41). Similar to other AGs, plazomicin showed lower in vitro efficacy against Stenotrophomonas maltophilia.…”
Section: Chemistry and Mode Of Actionmentioning
confidence: 89%
“…Further more, Walterspiel et al [10] compared the inactivation of isepamicin, amikacin and gen tamicin by nine (1-lactams and two (l-lactam in- hibitors and concluded that isepamicin was su perior to gentamicin and at least as stable as amikacin, a property that constitutes an ad vantage in the monitoring of drug levels in pa tients with renal failure [11]. Studies on the post-antibiotic effect have shown that isepa micin was similar to netilmicin and gentamicin but had a faster activity [12].…”
Section: Materials and M Eth Ods Resultsmentioning
confidence: 99%